Sharia Law and Minority Civil Rights: The Access of Non-Muslims to Bureaucracy and Public Services in the Aceh Province - Alkhair, Rayyan; Muhtada, Dani; Irawaty, Irawaty; Ningsih, Ayup Suran (Universitas Negeri Semarang, 2025)
The objective of this article is to examine the extent to which the implementation of Islamic law in Aceh has affected the civil rights of non-Muslim groups. Its focus is on their access to bureaucracy and public services after the implementation of Islamic sharia. The article seeks to answer these questions: (1) What is the opinion of the non-Muslim communities in Aceh on the implementation of Sharia law and its impacts on their lives in Aceh? (2) Do they experience discrimination when it comes to bureaucracy, government, and access to public services after the special autonomy status granted in Aceh? (3) What is the strategy for strengthening access to bureaucracy and public services for non-Muslim community in Aceh? To answer this question, the author conducted research using a qualitative approach with a purposive sampling technique involving seven informants ranging from local bureaucrats, interfaith leaders and non-moslem NGO to utilizes in-depth explanation to assess the accessibility of public services and bureaucratic systems under the implementation of Sharia law. The article indicates that there has been a shifting opinion among non-Muslims in Aceh before and after the implementation of Islamic Sharia in Aceh. Before the implementation of Islamic law, they had a slanted view of Islamic law. But after the implementation of Islamic Sharia, their views have changed positively. When dealing with bureaucracy and public services, non-Muslims generally do not feel any discrimination. However, there have been instances where non-Muslims faced difficulties in obtaining permits for activities.